2012
DOI: 10.3897/phytokeys.19.3912
|View full text |Cite
|
Sign up to set email alerts
|

Chilean Pitavia more closely related to Oceania and Old World Rutaceae than to Neotropical groups: evidence from two cpDNA non-coding regions, with a new subfamilial classification of the family

Abstract: The position of the plant genus Pitavia within an infrafamilial phylogeny of Rutaceae (rue, or orange family) was investigated with the use of two non-coding regions from cpDNA, the trnL-trnF region and the rps16 intron. The only species of the genus, Pitavia punctata Molina, is restricted to the temperate forests of the Coastal Cordillera of Central-Southern Chile and threatened by loss of habitat. The genus traditionally has been treated as part of tribe Zanthoxyleae (subfamily Rutoideae) where it constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 64 publications
(125 reference statements)
2
56
0
Order By: Relevance
“…The close relation to Dictamnus was confirmed in a study by Groppo et al (2012). Groppo et al (2012) furthermore propose a new subfamilial structure of the Rutaceae with only two subfamilies, Cneoroideae and Rutoideae. According to this re-classification, Skimmia now belongs to the subfamily Rutoideae while it was formerly placed in Toddalioideae.…”
Section: Phylogenysupporting
confidence: 60%
See 1 more Smart Citation
“…The close relation to Dictamnus was confirmed in a study by Groppo et al (2012). Groppo et al (2012) furthermore propose a new subfamilial structure of the Rutaceae with only two subfamilies, Cneoroideae and Rutoideae. According to this re-classification, Skimmia now belongs to the subfamily Rutoideae while it was formerly placed in Toddalioideae.…”
Section: Phylogenysupporting
confidence: 60%
“…Both genera together form a well-supported clade with the genus Dictamnus (Salvo et al, 2008). The close relation to Dictamnus was confirmed in a study by Groppo et al (2012). Groppo et al (2012) furthermore propose a new subfamilial structure of the Rutaceae with only two subfamilies, Cneoroideae and Rutoideae.…”
Section: Phylogenysupporting
confidence: 53%
“…In the studies by Groppo et al (2012), although focused mainly on subfamily and tribe levels, only one species of Metrodorea was included and it emerged as sister to Esenbeckia, and conformed a clade with the other two sister genera Balfourodendron and Helietta. In the present study, however, Esenbeckia was not found as sister to Metrodorea.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…All 6 species of Metrodorea were included in our analyses. Out-groups (Nixon and Carpenter, 1993) were selected based on previous studies (Engler, 1931;Groppo et al, 2012) from i) all other genera of the same subtribe Pilocarpinae (Esenbeckia, Pilocarpus, and Raulinoa), ii) a genus of another subtribe (Galipeinae) in the same tribe Galipeeae (Galipea), and iii) three genera of other subfamilies (Balfourodendron, Helietta, and Zanthoxylum). We included one species for each genus represented in outgroups based on previous studies (Engler, 1931;.…”
Section: Taxon Samplingmentioning
confidence: 99%
See 1 more Smart Citation